The Impact of Internal and External Determinants on the Continuity of Profits for Commercial Banks, Applied Research in the Iraqi Commercial Bank for the period 2009- 2018 - Mashkour, SaoudChayed; Razaq Fullyh, Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze and discuss the object of the impact of internal and external determinants on the continuity of profits, as the internal determinants are indicators that affect the performance of banks and which can be controlled by the bank’s management and are under its control. Three internal determinants have been chosen, which are Capital Adequacy Ratio(CAR), asset quality (AQ) , and quick liquidity ratio(QLR). While the external determinants represents the macroeconomic indicators that affect the activities and performance of banks so that they cannot be controlled by banks because they are subject to economic variables and conditions. Twospecifics external determinants were chosen, namely the gross domestic product(GDP) and the annual inflation rate (IFN).This research was applied in the Iraqi Commercial Bank listed on the Iraq Stock Exchange for the period 2009-2018. The descriptive analytical approach was used to describe, analyze and measure all variables through the actual financial data available from the bank, with the aim of evaluating and measuring independent and dependent research variables, and analysis of the correlation and impact relationship between them, as the analysis of variance using the program (spss) was used to measure the relationship of correlation and impact between the results of the internal and external determinants used in the research and the continuity of profits.This research reached a set of conclusions, the most important of which is that there is a correlation with a significant statistical effect and significance for all determinants with the continuity of profits, as the results of the research showed that the effect of the variables (capital adequacy ratio, liquidity and gross domestic product) had a positive effect on the continuity of profits, while the effect of asset quality and annual inflation rate was an inverse relationship with continuing profits.